2015
DOI: 10.1039/c4tb01693a
|View full text |Cite
|
Sign up to set email alerts
|

A highly bioactive and biodegradable poly(glycerol sebacate)–silica glass hybrid elastomer with tailored mechanical properties for bone tissue regeneration

Abstract: A highly bioactive and biodegradable PGS–Silica bioactive glass hybrid elastomer with tailored mechanical properties was developed for bone tissue regeneration application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 53 publications
3
46
0
Order By: Relevance
“…As compared to pure CPC elastomers, the significant improvement of mechanical properties as the increase of silica content could be attributed to the high stiffness of inorganic silica networks (SiOSi) and molecular‐level distribution in polymer matrix. This result was in accordance with previous reports on silica‐based polymer hybrid biomaterials . The increase of cross‐linking temperature and HDI content significantly enhanced the mechanical strength, which was probably due to the increase of cross‐linked density (limiting the movement of polymer chain) (Figure ).…”
Section: Resultssupporting
confidence: 92%
“…As compared to pure CPC elastomers, the significant improvement of mechanical properties as the increase of silica content could be attributed to the high stiffness of inorganic silica networks (SiOSi) and molecular‐level distribution in polymer matrix. This result was in accordance with previous reports on silica‐based polymer hybrid biomaterials . The increase of cross‐linking temperature and HDI content significantly enhanced the mechanical strength, which was probably due to the increase of cross‐linked density (limiting the movement of polymer chain) (Figure ).…”
Section: Resultssupporting
confidence: 92%
“…However, it was not possible to observe the melting and crystallization temperatures in the heating and cooling cycles performed, respectively, which was due to a limitation of the instrument used in the study. In previous works Gaharwar et al [18] and Zhao et al [19] calculated the melting temperature at ≈10 °C. On the other hand, Wang et al [16] revealed two crystallization temperatures at −52.14 °C…”
Section: Discussionmentioning
confidence: 99%
“…The resulting hybrid polycitrate-silicon (PCS) elastomers demonstrated significantly improved elastomeric behavior, mechanical strength and cellular biocompatibility (Figure 7) [30]. SBGS-based PGS hybrid elastomers were also fabricated successfully through the direct hybridization of SBGS and PGS solution [29]. SBGS-PGS hybrid elastomers exhibited significantly enhanced mechanical properties, biominerialization and cellular biocompatibility (Figure 8).…”
Section: Synthesis and Properties Of Hybrid Polymersmentioning
confidence: 99%
“…Due to the inherent elastomeric behavior of native bone, elastomeric hybrid biomaterials are appealing for applications in bone regeneration [94]. Our group developed silicon-based polymer elastomers with controlled biodegradation for applications in bone regeneration [2931]. The results demonstrated that poly(citrate-siloxane) (PCS) hybrid elastomers significantly enhanced attachment and proliferation of various cells, including cells derived from both hard and soft tissue [30,31].…”
Section: Applications In Bone Tissue Regenerationmentioning
confidence: 99%
See 1 more Smart Citation